The state of the membrane potential of the mitochondria of blood leukocytes in acute coronary syndrome - P. A. Semenova; V. A. Nevzorova; N. G. Plekhova; I. N. Chernenko; E. K. Lemtyugova (Евразийский Кардиологический Журнал)
Purpose: to assess the state of mitochondrial membrane potential of blood leukocytes in acute coronary syndrome (ACS) depending on the presence and absence  of type 2 diabetes mellitus (T2DM).Material and Methods. The study involved 100 people hospitalized at the regional vascular center (RCC) of the Vladivostok  Clinical Hospital No. 1 with a diagnosis  of ACS, aged 35 to 65 years. The control group consisted of 30 apparently healthy volunteers of the same age and sex. At the time of admission,  all patients underwent  studies  for  the diagnosis  of ACS, including an assessment  of the content of troponin I (TrI),  and  the  marker of the precursor  of the cerebral  natriuretic peptide  (NTproBNP) and the membrane  potential of mitochondria  (MPM)  of blood  leukocytes were determined.Results. Indicators  of the state MMP made  it possible to assess the content of dead and living cells in the blood  of the examined persons.  An increase in non-viable  leukocytes  in the blood  patients with all types of ACS, including myocardial  infarction (MI)  and  unstable  angina  (UA),  was  established. A direct relationship was  found  between  the increase  in the number  of these cells and the content of TrI in MI and a direct  relationship  between it and NTproBNP both  in MI and NS. In patients with ACS, no  significant difference was found between the MMP values of leukocytes depending on the presence of T2DM.Conclusion. An increase  in the MPMP of blood  leukocytes  in patients accompanies of the redox  balance  disturbance  in ACS. The established relationship between  MPMP indices  in MI and the content  of TrI can  be considered as a confirming fact of the participation of cells with mitochondrial dysfunction in the development of ischemic necrosis. The found relationship between  the increase  in blood  leukocyte  MPMP in patients with ACS and the level of NTproBNP indicates  a certain contribution  of mitochondrial dysfunction of leukocytes to the development of myocardial remodeling, regardless of the clinical form of ACS and the presence of DM2.